A global horizon scan for urban evolutionary ecology. (November 2022) - Verrelli, Brian C.; Alberti, Marina; Des Roches, Simone; Harris, Nyeema C.; Hendry, Andrew P.; Johnson, Marc T.J.; Savage, Amy M.; Charmantier, Anne; Gotanda, Kiyoko M.; Govaert, Lynn; Miles, Lindsay S.; Rivkin, L. Ruth; et al.
Abstract : Research on the evolutionary ecology of urban areas reveals how human-induced evolutionary changes affect biodiversity and essential ecosystem services. In a rapidly urbanizing world imposing many selective pressures, a time-sensitive goal is to identify the emergent issues and research priorities that affect the ecology and evolution of species within cities. Here, we report the results of a horizon scan of research questions in urban evolutionary ecology submitted by 100 interdisciplinary scholars. We identified 30 top questions organized into six themes that highlight priorities for future research. These research questions will require methodological advances and interdisciplinary collaborations, with continued revision as the field of urban evolutionary ecology expands with the rapid growth of cities. Highlights: The impact of urbanization on biodiversity has been well documented, yet research into the complex dynamics of ecological and evolutionary processes in urban areas is still in its infancy. When novel research challenges emerge, a horizon scan exercise is an integrated approach that brings together global interdisciplinary-minded individuals to identify future research questions that can influence new collaborations and funding agenda. Our horizon scan identified 30 questions for future research in urban evolutionary ecology covering themes in fundamental ecological and evolutionary processes, temporal and spatial scales, sustainability, climate change, sociopolitical and ethical considerations, and innovation in technology.